On the Margins of Category. Liberty as Cooperation in a Non-Prototypical Neo-Sarmatian Novel - Bohuszewicz, Paweł (Literatura Ludowa. Journal of Folklore and Popular Culture, 2026)
The article contains an analysis of the book series Diabłu ogarek [Candle- End for the Devil] by Konrad T. Lewandowski. Its main goal is to show that the basic variety of Neo-Sarmatism, that is, right-wing Neo-Sarmatism, is not the only one, as there is a certain hidden potentiality in Sarmatism, realized by the novels under discussion. Against right-wing Neo-Sarmatism – resentimental (towards the broadly understood modernity), exclusive (towards subordinated groups, not included in Neo-Sarmatism) and patriarchal (“lordly”) – Lewandowski situates a world that can be termed as democratic in the broadest sense of the notion of democracy as extended to earthly and non-earthly beings, human and non-human ones, as well as regulating relations within the human world.